POLA PENGEMBANGAN KEBERBAKATAN DAN PEMBENTUKAN KEDISIPLINAN ANAK - Tahrir Tahrir (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2009)
Giftedness and discipline are important basic foundation for children to prepare their future. Thus, the development of giftedness and altering behavior with self disciplined regulation needs to be counted for by parents and teachers. Focusing on nurturing giftedness was considered important that children can prepare themselves to be professional individuals who know their strengths and weaknesses to face all aspects in life. In the other hand, discipline and self regulatory were set to prepare those children to have responsibilities and professional ethos both at work life and in personal life. Parents and teacher in this case need to provide time and design a systematic plan to develop their potential. An effective model for this purpose is a giftedness development and self regulatory training which were designed according to the principal of children’s development.